PERBEDAAN HASIL BELAJAR SISWA MATERI PERSAMAAN GARIS LURUS YANG MENGGUNAKAN MODEL PROBLEM BASED LEARNING DENGAN MODEL DIRECT INSTRUCTION DI SMP NEGERI 2 TOMPASO - Rori, Fitiyanto Eliezer; Mangobi, James; Sulistyaningsih, Murni (JURNAL LEMMA, 2025)
This study aims to compare the effectiveness of the Problem Based Learning (PBL) model with Direct Instruction (DI) in improving student learning outcomes on straight line equations. The focus of the research is to test whether the academic achievement of students taught through PBL is superior to those using DI. This study adopted a comparative method with a quasi-experiment design, specifically Post-test Only Control Group Design. The research subjects consisted of two homogeneous classes in level VIII: class VIIIA (as the experimental group) with 20 students who received PBL-based learning, and class VIIIB (as the control group) with 20 students who were taught through DI. Data were obtained from the post-test results of both classes after the learning intervention. Statistical analysis showed the average post-test score of the experimental class was 82.75, while the control class obtained an average of 74.95. Through hypothesis testing, the value of tcount = 2.178 and ttable = 2.0243 was obtained. Becausetcount> ttable, the null hypothesis(H₀) is rejected.  The results of the analysis prove that learning straight line equations using the PBL model results in significantly higher learning achievement than the application of the DI model. This finding corroborates the claim that the problem-based approach is more effective in improving students' understanding of the topic.